Against Violence In Luc Besson's The Lady Movie (2012) :An Individual Psychological Approach - Kurniawati, Dwi Novi; , Dr. Phil Dewi Candraningrum, S.Pd, M.Ed; , Siti Fatimah, S.Pd, M.Hum (2013)
The research investigates how the major character struggles to against violence in Luc Besson "The Lady" movie. Therefore, the study analyzes the movie in terms of its structural elements and based on the individual psychological approach.The object of the study is the personality of the major character of Aung San Suu Kyi. The data sources are literary data. Those are divided in two categories, primary data sources and secondary data sources. The primary data source is the movie itself. The secondary data sources are the other sources related to the movie. The method of data collection of the study is library research. The technique of data analysis is descriptive analysis.The outcome of the study shows that the struggle to against violence is the reflection of the woman trying to motivate, inspiration and free the Burma's people from the political violence for the democracy. The author wants to describe how woman have many efforts to save her mother land, it is showed that not just the man who can do it but woman also can do it.